(untitled) (Revista de Medicina Clinica, 2024)
Celiac disease (CD) is an autoimmune disorder triggered by gluten ingestion in genetically predisposed individuals, marked by inflammation and the production of anti-tissue transglutaminase antibodies. Although CD patients often have lower body mass indexes and LDL levels, systemic inflammation can lead to endothelial dysfunction and accelerated atherosclerosis, potentially increasing the risk of coronary artery disease (CAD). We present a case of a 46-year-old female with CD who developed multivessel CAD, ultimately requiring coronary artery bypass grafting. This case highlights the significant cardiovascular risk associated with CD, suggesting that inflammation and genetic factors may contribute to atherosclerosis. While the precise mechanisms remain unclear, the findings underscore the need for vigilant cardiovascular monitoring in CD patients and further research to explore the impact of gluten-free diets on cardiovascular health.